The Relationship between Intelligence Level and Social Interaction Ability in Mentally Retarded Children at SLB (Special School) of Idayu 2 Pakis Malang - Rahayu, Putri Ida; Ira Handian, Feriana (Universitas Airlangga, 2022)
ABSTRACT Introduction: Children with mental retardation tend to have intellectual limitations than average and are along with impaired social adjustment abilities. Therefore, mentally retarded children experience social communication difficulties, even communication. This study aims to analyze the relationship between intelligence level and social interaction skills in mentally retarded children at SLB Idayu Pakis Malang. Methods: The design of this study was quantitative with a cross sectional approach. The population in this study were Idayu Special School students with mental retardation with a sample size of 30 respondents. The sampling technique uses total sampling. The data collection was using a documentation sheet based on reports from teachers for IQ scores and checklist sheets adapted from Vineland-3. Results: The results of the analysis obtained p = 0.000 with p value < 0.05 and (r) 0.648. This result showed a correlation between intelligence level and social interaction ability in mentally retarded children at SLB Idayu Pakis Malang. This research is expected could be used as a reference in adding guidance to mentally retarded children in order to develop intellectual skills to improve their social interaction skills through play therapy activities.